1976
DOI: 10.1007/bf01175568
|View full text |Cite
|
Sign up to set email alerts
|

A nucleolus-associated coiled body

Abstract: One or two healthy structures frequently have been observed attached to nucleoli in facial motor neurons of the golden hamster. These round-to-oval structures, called "coiled bodies", were seen at 15, 19, and 24 days postnatal and in the adult, both in normal neurons and in chromatolytic neurons which had been axotomized 4 days previously. With one exception, the coiled bodies were seen to be attached via fibrillar material to the nucleolar periphery. Although the numbers of coiled bodies may be altered during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
4
8
0
Order By: Relevance
“…We prepared total protein extracts using Drosophila PARP1 mutant stock ubiquitously expressing PARP1-ECFP or PARPe-EGFP transgenic constructs. First, we found that PARP1-ECFP, as well as PARPe-EGFP, proteins always co-purify with Coilin, as well as Fibrillarin protein (Figure 1D), which has also been reported as a component of CBs [18]. Additional co-immunoprecipitation experiments with anti-Fibrillarin antibody confirmed the specificity of PARP1-Fibrillarin interaction (Figure S2A).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…We prepared total protein extracts using Drosophila PARP1 mutant stock ubiquitously expressing PARP1-ECFP or PARPe-EGFP transgenic constructs. First, we found that PARP1-ECFP, as well as PARPe-EGFP, proteins always co-purify with Coilin, as well as Fibrillarin protein (Figure 1D), which has also been reported as a component of CBs [18]. Additional co-immunoprecipitation experiments with anti-Fibrillarin antibody confirmed the specificity of PARP1-Fibrillarin interaction (Figure S2A).…”
Section: Resultssupporting
confidence: 67%
“…Since PARP1 protein also controls transcription and nucleoli and since automodified PARP1 is targeted into CB, PARP1 could be an important link in this process. Moreover, CBs are often seen attached to the nucleolus and share many nucleolar protein components, such as protein Fibrillarin [18] and p80 protein coilin which is a common specific marker of CBs [19] that we have used in our experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The coiled body is formed of a group of dense, distinct elements referred to as "coils" (Fig. 3) in other cell types (Kinderman and LaVelle, 1976;Schultz, 1989) that show moderate to high affinity for heavy metal salts. The more electron-opaque coils are 13-49 nm wide (X = 32, SD = 9, n = 34) and up to 120 nm long.…”
Section: Coiled Bodymentioning
confidence: 99%
“…Intranuclear granular inclusions are frequently associated with another inclusion body, which is round in shape and measures about 0.5 pm in diameter; the body is not bounded by a membrane and is composed of electron-opaque, irregularly arranged strands consisting of granular and filamentous elements and intervening material of low electron opacity . This nuclear inclusion may correspond to coiled bodies or similar structures called by different names which are described in nerve cells [Hardin et al, 1969;Grillo, 1970;Le Beux, 1971;Kinderman and LaVelle, 1976;HervLs et al, 1980;Lafarga et al, 1983a1, immature glial cells [Lafarga et al, 1983b1, and nonneuronal cells [Monneron and Bernhard, 19691. In cotton rat pinealocytes, coiled bodies are usually localized distant from the nucleolus.…”
Section: Resultsmentioning
confidence: 99%